Social Media Travel Influencers: Strategic Insights and Impact on Domestic Travel Decision Making by Thai Millennials - Sutasinee Na Nakhon (Prince of Songkla University, 2023)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2022